Network Analysis of the Systemic Response to Fasciola hepatica Infection in Sheep Reveals Changes in Fibrosis, Apoptosis, Toll-Like Receptors 3/4, and B Cell Function - Fu, Yan; Browne, John A.; Killick, Kate; Mulcahy, Grace (Frontiers in Immunology, 2017)
The trematode Fasciola hepatica is an important cause of disease in livestock and in man. Modulation of immunity is a critical strategy used by this parasite to facilitate its long-term survival in the host. Understanding the underlying mechanisms at a system level is important for the development of novel control strategies such as vaccination, as well as for increasing general understanding of helminth-mediated immunoregulation and its consequences. Our previous RNA-seq work identified a large number of differentially expressed genes (DEG) from ovine peripheral blood mononuclear cells (PBMC) at acute and chronic stages of F. hepatica infection, and yielded important information on host-parasite interaction, with particular reference to the immune response. To extend our understanding of the immunoregulatory effects of this parasite, we employed InnateDB to further analyze the DEG dataset and identified 2458 and 224 molecular interactions in the context of innate immunity from the acute and chronic stages of infection, respectively. Notably, 458 interactions at the acute stage of infection were manually curated from studies involving PBMC-related cell-types, which guaranteed confident hypothesis generation. NetworkAnalyst was subsequently used to construct and visualize molecular networks. Two complementary strategies (function-first and connection-first) were conducted to interpret the networks. The function-first approach highlighted subnetworks implicated in regulation of TLR3/TLR4 signaling in both acute and chronic infection. The connection-first approach highlighted regulation of intrinsic apoptosis and BCR-signaling during acute and chronic infection, respectively. To the best of our knowledge, this study is the first system level analysis of the regulation of host innate immunity during F. hepatica infection. It provides insights into the profound changes induced by F. hepatica infection, that favors parasite survival into chronic infection, but also impede the host’s immune response to other pathogens, and render vaccination against fasciolosis a difficult challenge. The information provided will be useful in the design of specific vaccine protocols to overcome parasite-mediated immunoregulation, and in furthering general understanding of the interplay between helminth infection and host immune systems.